Advances in Dry Eye Disease Examination Techniques - Wu, Yaying; Wang, Chunyang; Wang, Xin; Mou, Yujie; Yuan, Kelan; Huang, Xiaodan; Jin, Xiuming (Frontiers in Medicine, 2022)
Dry eye-related ocular surface examination is very important in the diagnosis and treatment of dry eye disease. With recent advances in science and technology, dry eye examination techniques have progressed rapidly, which has greatly improved dry eye diagnoses and treatment. However, clinically, confusion remains about which examination to choose, how to ensure the repeatability of the examination, and how to accurately interpret the examination results. In this review, we systematically evaluate previous examinations of dry eye, analyze the latest views and research hotspots, and provide a reference for the diagnosis and management of dry eye.